2022
DOI: 10.3390/ani12080950
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Water Level Fluctuation on Zooplankton Communities in Shahu Lake Based on DNA Metabarcoding and Morphological Methods

Abstract: Background: The water level of Poyang Lake (China) fluctuates seasonally. Shahu Lake, a smaller body of water connected to Poyang Lake during the wet season, is separated in the dry season. Due to a special fishing method termed ‘lake enclosed in autumn’, the water level is lowered and reaches its lowest point in January, which is <0.5 m deep in the middle of the lake. Our research investigated the effect of water level changes on the zooplankton community composition in Shahu Lake. Methods: We used both DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
2
2
0
Order By: Relevance
“…Meanwhile, greater overlap was observed for bird and fish species, with 8/11 bird species and 10/15 fish species detected in the eDNA versus conventional methods used here (Reeves, 2011; https://nzffdms.niwa.co.nz/). These patterns are consistent with other research, where eDNA has detected more zooplankton species than morphological‐based methods in marine and lake environments (Qiu et al., 2022; Suter et al., 2021). Similarly, Mejia et al.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Meanwhile, greater overlap was observed for bird and fish species, with 8/11 bird species and 10/15 fish species detected in the eDNA versus conventional methods used here (Reeves, 2011; https://nzffdms.niwa.co.nz/). These patterns are consistent with other research, where eDNA has detected more zooplankton species than morphological‐based methods in marine and lake environments (Qiu et al., 2022; Suter et al., 2021). Similarly, Mejia et al.…”
Section: Discussionsupporting
confidence: 92%
“…nz/ ). These patterns are consistent with other research, where eDNA has detected more zooplankton species than morphologicalbased methods in marine and lake environments (Qiu et al, 2022;Suter et al, 2021). Similarly, Mejia et al (2021) observed low concordance between a botanist survey and eDNA results at Mojave Desert Springs.…”
Section: Discussionsupporting
confidence: 89%
“…Owing to these advantages, eDNA analyzers have been actively applied to abundance and species diversity monitoring based on zooplankton abundance. Recent studies have suggested that eDNA analysis methods can identify biodiversity with equal or better performance than morphological analysis methods [105,106]. For example, in the analysis of seasonal changes in zooplankton α-diversity, metabarcoding showed a consistent relationship with morphological methods in identifying changes in species composition of zooplankton and species diversity of Copepoda; 37 species were detected by metabarcoding analysis and 11 species by morphological analysis, demonstrating the applicability of eDNA analysis methods in monitoring species diversity [106].…”
Section: Application Of Edna To the Development Of Zooplankton Indicesmentioning
confidence: 98%
“…Climate change and rainfall variability will magnify the water level uctuations that (Heinsalu et al, 2008) affect the physicochemical variables and the functioning of an aquatic environment (Liu et al, 2019), potentially altering the biological communities of lake ecosystem (Kobayashi et al, 2020). The diversity and abundance of zooplankton community are largely in uenced by the amplitude of water-level regims (Chaparro et al, 2019;Hu et al, 2019;Wang et al, 2019;Tan et al, 2021;Qiu et al, 2022). How ever, little is known about the effect of water level uctuations in deep tropical lakes.…”
Section: Introductionmentioning
confidence: 99%